El Deporte en Costa Rica, su acceso y práctica como un Derecho Humano - Vargas Chaverri, Luis Gabriel (2026)
The legal nature of Soft Law is analyzed in the Costa Rican legal system and the application with the article 48 of the Constitution. Subsequently, an analysis of various jurisprudence is carried out and it is related to the access and practice of sport as a human right, which would generate a paradigm shift in Costa Rican society.